2019
DOI: 10.3390/v11060573
|View full text |Cite
|
Sign up to set email alerts
|

Susceptibility of Chickens to Porcine Deltacoronavirus Infection

Abstract: Porcine deltacoronavirus (PDCoV) is a novel swine enteropathogenic coronavirus with worldwide distribution. PDCoV belongs to the Deltacoronavirus (DCoV) genus, which mainly includes avian coronaviruses (CoVs). PDCoV has the potential to infect human and chicken cells in vitro, and also has limited infectivity in calves. However, the origin of PDCoV in pigs, the host range, and cross-species infection of PDCoV still remain unclear. To determine whether PDCoV really has the ability to infect chickens in vivo, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
81
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 105 publications
(89 citation statements)
references
References 31 publications
8
81
0
Order By: Relevance
“…Pig infection dynamics have demonstrated a similar serum Recent studies demonstrated that PDCoV can infect and kill cells of other species through APN receptors (19,35). PDCoV has been reported to infect commercial chickens in vivo (36). The differences in susceptibility to PDCoV infection between chicks and poults we observed could be related to differences in APN expression levels between the species.…”
Section: Discussionsupporting
confidence: 67%
“…Pig infection dynamics have demonstrated a similar serum Recent studies demonstrated that PDCoV can infect and kill cells of other species through APN receptors (19,35). PDCoV has been reported to infect commercial chickens in vivo (36). The differences in susceptibility to PDCoV infection between chicks and poults we observed could be related to differences in APN expression levels between the species.…”
Section: Discussionsupporting
confidence: 67%
“…Importantly, porcine aminopeptidase N (pAPN) has been reported to serve as a functional receptor for PDCoV in two recent studies [24,25], and the virus may engage APN from diverse species to facilitate its interspecies transmission [25]. Recently, PDCoV has been reported to successfully infect chickens and calves [26,27]. Thus, PDCoV must be studied more extensively to better understand its emergence, lifecycle, evolution and pathogenesis in order to facilitate future control of the virus.…”
Section: Introductionmentioning
confidence: 99%
“…Subsequently, PDCoV was identified in South Korea, Canada, Mainland China, Thailand, Lao People's Democratic Republic and Vietnam (Lee and Lee, 2014;Saeng-Chuto et al, 2017;Song et al, 2015;Dong et al, 2015). Furthermore, recent studies reported that calves and chickens are also susceptible to PDCoV (Jung et al, 2017;Liang et al, 2019), and that PDCoV possesses the potential to infect humans (Li et al, 2018), highlighting a possible cross-species transmission related to this emerging virus.…”
Section: Introductionmentioning
confidence: 99%